Association between atherogenic index of plasma and risk of type 2 diabetes mellitus and the mediating effect of BMI: a comparative analysis in Chinese and Japanese populations - Yuheng Liao; Yong Han; Changchun Cao; Haiying Song; Haofei Hu (Diabetology & Metabolic Syndrome)
Abstract Objective The atherogenic index of plasma (AIP) has emerged as a promising predictor for type 2 diabetes mellitus (T2DM), but population-specific patterns and underlying mechanisms remain poorly understood. This study investigated the association between AIP and T2DM risk in Chinese and Japanese populations, focusing on non-linear relationships, population-specific thresholds, and the mediating role of body mass index (BMI). Methods We conducted a retrospective cohort study using data from the China Rich Healthcare Group (n = 112,483) and the Japanese NAGALA database (n = 15,453). AIP was calculated as log10[triglyceride (TG)/high-density lipoprotein cholesterol (HDL-C)]. T2DM was defined as fasting plasma glucose (FPG) ≥ 7.0 mmol/L, hemoglobin A1c (HbA1c) ≥ 6.5%, or self-reported diabetes during follow-up. Cox proportional hazards models with restricted cubic splines were used to examine non-linear relationships. Two-piecewise regression models identified population-specific thresholds, and formal mediation analyses quantified BMI’s mediating effect. Results During a median follow-up of 3.0 years, 1,801 participants (1.41%) developed T2DM. AIP demonstrated a significant positive association with T2DM risk in both populations: hazard ratio (HR) per unit increase: Chinese 1.84, 95% confidence interval (CI) 1.54–2.21; Japanese 2.42, 95% CI 1.67–3.52) after comprehensive adjustment. We identified distinct population-specific non-linear relationships with different threshold effects: in Chinese participants, T2DM risk increased significantly until AIP reached 0.436, while in Japanese participants, significant risk elevation began at AIP values exceeding − 0.449. BMI mediated a considerably higher proportion of the total effect in Chinese (39.84%) compared to Japanese participants (27.11%), indicating differential pathophysiological mechanisms. Conclusions Our findings reveal substantial population-specific differences in the AIP-T2DM relationship, including population-specific thresholds and mediation pathways. These results underscore the importance of population-tailored screening strategies and suggest that interventions targeting lipid metabolism and BMI management may have varying efficacy across East Asian populations.